Attitudes and views regarding law enforcement activity at large outdoor raves in Israel: a cross-sectional survey - Shapira, Barak (Policing and society, 2023)
Harm reduction services, such as drug testing kiosks and ‘safe zones’ are often advocated for reducing the harms of drug use among rave and festival attendees. However, interaction with law enforcement can undermine efforts at introducing formal harm reduction services. This cross-sectional, client-oriented study aims to frame the potential components of a tolerance-based policy in outdoor raves in Israel, which assumes a continued police presence, and availability of harm reduction services. The study described the views of outdoor rave attendees towards the role of police, willingness to use harm reduction services, and help-seeking behaviours. Overall, participants reported negative attitudes towards current policing at outdoor raves and a low intention-to-seek help from the police when in physical or emotional distress. Only 13% of responders viewed police presence at raves as important for keeping event areas safe. Furthermore, 85% claimed police presence would prevent them from using drug testing services if these become available. Report of lifetime drug use at raves was significantly and inversely associated with willingness to seek help from the police in cases of physical or emotional distress (Odds Ratio = 0.15, Confidence Interval: 0.08, 0.30). This negative perception of police presence at large outdoor raves indicates low support and trust for current policing approaches, and that these approaches may be a barrier to the introduction of formal harm reduction services under the current prohibitionist approach. These results underpin the need to reform current law enforcement practices towards tolerance-based approaches that permit access to harm reduction services.